Construction and immunohistochemical validation of a necroptosis-related prognostic signature in bladder cancer and its association with tumor immune infiltration - Wang, Tao; Ding, Fei; Sun, Kai (Frontiers in Genetics, 2025)
BackgroundBladder urothelial carcinoma (BLCA) represents a highly malignant neoplasm with significant clinical challenges. Necroptosis, a programmed form of cell death, exhibits dual regulatory functions in both tumor immunomodulation and oncogenesis. The precise mechanistic involvement of necroptosis-related genes (NRGs) in BLCA pathogenesis remains poorly characterized, prompting our systematic investigation of their potential biological and clinical significance.Methods and resultsWe performed comprehensive bioinformatics analyses utilizing integrated datasets from The Cancer Genome Atlas (TCGA) and the Gene Expression Omnibus (GEO) database. Through the Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway annotation, we curated 159 NRGs and subsequently identified 25 differentially expressed genes functionally implicated in necrotic cell death and extrinsic apoptotic pathways, specifically including influenza A signaling, NOD-like receptor cascades, and related biological processes. Univariate Cox proportional hazards modeling coupled with LASSO regression analysis revealed five prognostically significant NRGs (CAMK2A, CHMP4C, IL33, IRF9, and TRAF5). Based on these genes, we developed a robust prognostic model that can stratify patients into high- and low-risk categories, each exhibiting distinct survival outcomes. This model demonstrated moderate accuracy in prognosis prediction. Immunohistochemical validation in BLCA specimens confirmed dysregulated expression patterns of these five NRGs. Additional analyses uncovered significant correlations between NRG expression profiles and various immunological parameters, including immune cell infiltration patterns and immune checkpoint molecule expression.ConclusionOur study delineates a novel five-gene NRG signature with robust prognostic value in BLCA. These gene determinants appear to critically influence both tumor progression and immune microenvironment, thereby representing promising candidates for therapeutic targeting and future mechanistic exploration in bladder cancer biology.